Permanent preservation, coverage area and use of the land in the hydrographic basin of the Almas River, microregion de Ceres, Goiás, Brazil - Da Silva Barbalh, Maria Gonçalves; De Andrade Franco, José Luiz; Leal, Antonio Cezar [UNESP]; De Castro Peixoto, Josana (Editora de Livros IABS, 2019)
The aim of this study was to map the Permanent Preservation Areas (PPAs), as well as land cover and land use in the Almas River basin in Goiás, Brazil, based on geoprocessing. The results showed the remnants of the original vegetation are limited to fragments and occupy 32.52% of the area. Grassland is the dominant use, which is distributed throughout the area. Sugar cane and grains secondarily occupy other areas of the river basin. The mapped permanent preservation areas occupy an area of 1,182.22 km2, representing only 11.53% of the basins total area. The PPAs located on slopes with a 45° had a smaller area mapped and they were less affected by the use, whereas those of PPAs located in the springs and watercourses with larger area. Land use, disregarding APP areas, can endanger vital areas that, if degraded, represent damage to water resources.
Áreas de preservação permanente, cobertura e uso da terra da bacia hidrográfica do rio das Almas, microrregião de Ceres, Goiás, Brasil
Keywords: Classification based on objects; Environmental management; Mapping; Sustainability